(untitled) (Herald of Journalism, 2020)
TV-television is not only mass communication, but a kind of creation. Every kind of creation have specific art language. The nature of commu- nication demand from TV journalists to speak with auditorial on modern language. The personal factor is playing a big role on TV. The work of broadcasting journalist demand of professional skills, which cultivate via training, theoretical and practical experience, width prospect, erudition, ability to communicate with people, to be inquisitive.